Nitrogen losses from hard red spring wheat fields in the northern plains. (6th April 2021) - Chatterjee, Amitava; Veverka, Donald; Carlson, Melissa
Abstract: Nitrogen dynamics varies spatially in response to complex interactions among weather, soil, and management practices. Twenty‐six spring wheat ( Triticum aestivum L.) fields were studied for N losses, nitrous oxide (N2 O) flux and ammonia (NH3 ) volatilization, grain yield and protein concentration in farmers fields in Minnesota and North Dakota of the Red River Valley during 2018– 2020 growing seasons. Spring wheat grain yield ranged from 2.8 to 9.7 Mg ha –1 with protein concentration ranging between 106 and 180 g kg –1 . Average cumulative N2 O and NH3 losses were 415 g N2 O‐N ha –1 and 1.43 kg NH3 ha –1, respectively ( n = 26). Spring wheat grain yield ( r = .53, p = .01) had positive association with May rainfall. Grain protein concentration declined with delay in planting ( r = –0.55, p = .01). Linear regression indicates a close association of daily N2 O flux with soil moisture ( r 2 = .23, p < .01), soil inorganic N concentration ( r 2 = .02, p = .04), and days after planting ( r 2 = .20, p < .01). Soil inorganic N concentration (just after planting) had a positive association with cumulative N2 O flux ( r = .41, p = .03). This study showed rainfall, soil moisture, and inorganic N concentration play a dominant role in N dynamics across the region. Core Ideas: Grain yield positively related to May rainfall. Protein concentration declined with delay in planting date. Daily N2 O flux positively related to soil moisture content. Cumulative N2 O‐N loss increased with high initial soil inorganic N.